Corruption as a Deviation from Islamic Economic Values (A Literature Study from a Sharia Ethics Perspective) - Tirta Zaharani; Dwi Gita Meilani; Nabila Islami Putri Irawan; Havis Aravik (Publication and Inovasi Research, 2025)
Corruption is a social phenomenon that not only causes material losses but also reflects moral and ethical deviations within the economic system. From the perspective of Islamic economics, corruption is considered a serious violation of Sharia values that uphold justice (‘adl), trustworthiness (amanah), honesty (ṣidq), and public welfare (maṣlaḥah). This study aims to analyze corruption as a deviation from Islamic economic values through the lens of Sharia ethics. The research employs a library-based study by examining primary and secondary sources, including the Qur’an, Hadith, classical Islamic jurisprudence texts, and relevant contemporary academic literature. The findings indicate that corrupt practices fundamentally contradict the core principles of Islamic economics, particularly the prohibitions of ghulul (embezzlement), risywah (bribery), and betrayal of trust (khianat), while also undermining the objectives of Islamic law (maqāṣid al-sharī‘ah), especially the protection of wealth (ḥifẓ al-māl) and social justice. From the perspective of Sharia ethics, corruption is not merely a legal violation but represents a moral and spiritual failure of both individuals and institutions. Therefore, combating corruption within an Islamic economic framework requires a comprehensive approach that integrates ethical reinforcement, personal integrity, and institutional reform grounded in Sharia principles...